Fuzzy PI controller for DC motor speed control - Ambata, Leonard U. (Animo Repository, 2024)
It has been a practice in control system design to provide certain means of control in any control system by using different techniques such as adding compensators like PI, PD, and PID, with the incorporation of machine intelligence techniques such as fuzzy logic, artificial neural networks, and evolutionary computation.This paper presents a discussion in the development of compensators for control systems using the hybrid of the conventional proportional-integral (PI) method and fuzzy logic. The development of the so-called "fuzzy-PI controller" is discussed with some experimental results gathered from its application of speed control for de motor.